The Effect Of Guided Imagery Based On Spiritual Care On Stress Level And Blood Pressure Of Hypertension Patients - Agustina Ekawati; Ah Yusuf; Wesiana Heris Santy (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Stress and increased blood pressure experienced by a person are factors that cause hypertension. Hypertension that is not realized and not treated immediately can cause various complications that can end in death. Methods: The sample size is 34 respondents, and the sampling technique is purposive sampling. The intervention group was given Guided Imagery-Based On Spiritual Care for 15-20 minutes, and the control group was given standard intervention (usual care) for one week. The variables studied were stress levels and blood pressure. The analysis used the Wilcoxon Signed Rank Test for pre and post-treatment as well as the Mann-Whitney test to determine the difference between the intervention group and the control group, with a significant value of <0.05. Results The results of the analysis of systolic blood pressure using the Wilcoxon Signed Rank Test showed a p-value of 0.001 in the intervention group and a p-value of 0.564 in the control group. The results of the analysis of Diastolic Blood Pressure using the Wilcoxon Signed Rank Test were a p-value of 0.003 in the intervention group and a p-value of 0.046 in the control group. The results of the analysis using Mann-Whitney obtained a p-value of 0.000 stress, a Systolic Blood Pressure p-value of 0.000, and a Diastolic Blood Pressure p-value of 0.000 between the intervention group and the control group. Conclusion Guided Imagery-Based Spiritual Care is effective in reducing stress levels and blood pressure of hypertensive patients. This technique is easy to do, so it can be applied as a nursing intervention in inpatient rooms for the development of nursing science in hospitals.